Design of multimedia blockchain privacy protection system based on distributed trusted communication. Issue 2 (5th April 2020) - Li, Daming; Liu, Wenjian; Deng, Lianbing; Qin, Bin
Abstract: Blockchain is a hash chain with chain structure formed by data blocks in chronological order. With the promotion of bitcoin, the research and application of blockchain, the underlying core technology of bitcoin, is growing rapidly, which is considered to be the fifth generation of Internet disruptive technology after mobile Internet. At present, there are various identity management applications and platforms based on blockchain, but while blockchain has gradually become the cornerstone of the value Internet, it also brings great challenges to the privacy protection needs of users. This article analyzes the privacy protection mechanism of blockchain network layer, transaction layer and application layer, including malicious node detection and access restriction technology in network layer, mixed currency technology and encryption technology in blockchain transaction layer. In this article, distributed communicable network technology and multimedia data security technology are used to build a blockchain security system. We designed the efficient system to accurately analyze the data and the information protection. The experimental results show that the proposed method has better data security guarantee ability. Abstract : Schematic diagram of DWCS system.